MARINE ECOTOURISM DEVELOPMENT STRATEGY AT THE COASTOF THE LAGUNA SAMUDRA, KAUR REGENCY, BENGKULU PROVINCE - Lucky Rahman; Dessy Yoswaty; Sofyan Husein Siregar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted in June-August 2019 at the coast of the Laguna Samudra, Kaur Regency, Bengkulu Province. The research aim to find out the potential of marine ecotourism and the development strategy at the coast of Laguna Samudra.This research uses a survey method.Resultsshown thatthe coast of Laguna Samudrahas suitable potential to be developed as a marine ecotourism area. The results of calculations on the value of land suitability index for recreational marine tourism category are 85.2%. Indicates that their value wasthe coastal of Laguna Samudra is very suitable to be uses a marine ecotourism destination. The SWOT analysis shows us a several alternative management strategies that are appropriate for the development of marine ecotourism on the coast of Laguna Samudra. The strategies uses include the Strategy Strength-Opportunity, namely make a general management plan (General Management Plan), improvement of local community development on ecotourism. Weakness-Opportunity Strategy, namely increased promotion in various social media,improve coordination between policy makers and managers, and improve the quality of human resources (HR). Keyword: Potential, Marine Ecotourism, SWOT analysis, Laguna Samudra Beach